Size-dependent chemical depletion of sediments in glacial environments: a case study of Mandakini Valley, central Himalaya, India. Issue 3 (17th February 2021) - Shukla, Tanuj; Kumar, Vinit; Mehta, Manish; Kotlia, Bahadur S.; Meenakshi,; Mal, Suraj
ABSTRACT: The size-dependent chemical maturity of sediment cycling in a high-altitude glacial/periglacial environment was studied by examining the sediments of the Chorabari Glacier, Mandakini Valley, central Himalaya, India. Sediments evacuated from glacial debris and a periglacial area were studied via particle-size analysis, X-ray fluorescence, and X-ray diffraction of different grain-size fractions. The results suggest a clear control of grain-size fraction over chemical weathering and release of its attendant nutrients from the glacial substrate. Elemental indices suggest the release of nutrients is principally controlled through comminution and sub-glacial chemical weathering of leachable minerals such as feldspar, mica, and apatite. Owing to biogeochemical cycles, the release of nutrients like phosphorous and calcium is predominantly controlled through mineral dissolution process of aluminosilicate rocks containing apatite, carbonate minerals and organic complexes. Overall, the size-dependent chemical maturity of glacial sediments suggests a much more chemically active system than previously thought. This study is of particular importance for downstream weathering tracer studies of detrital sediments.